Two-warehouse deterministic inventory model of expiry date known deteriorating items with just-in-time purchases for slotted backlogs - Thilagavathi, R.; Viswanath, J.; Mahdal, Miroslav; Udaya Prakash, Jayavelu; Salunkhe, Sachin (Frontiers in Applied Mathematics and Statistics, 2025)
IntroductionA two-warehouse deterministic inventory system for purchases of short-expiry items with low purchasing costs is modelled. The total cost of the replenishment cycle is arrived at by implementing multiple just-in-time (JIT) purchases for the slotted backlogged customers. It avoids the loss of impatient customers who are virtually waiting for a long time.MethodsThe inventory system consists of an own warehouse (OW) with finite capacity and an integral rental warehouse (RW) with unlimited capacity. Handlingand selling items with short expiry is a challenging task in revenue generation in commercial inventory management. Two categories of identical items are purchased: Category 1 consists of items whose expiry date falls within the replenishment cycle period, while Category 2 includes items with longer expiry dates. Unlike the traditional assumption in the literature, the items in Category 1 are purchased for a low price and stored in RW. Items in Category 2 are stored in OW. Due to short expiry of items, demands are first satisfied from the RW. The items in the RW are emptied before the expiry date of the items, due to expiry date-dependent deterioration and constant demand. At the same time, the items in the OW are decreasing due to exponential demand and constant deterioration. All customers are backlogged during the stock-out period and slotted into three intervals. The finite number of JIT purchases is employed to satisfy the backlogged slotted demands that occur before the last slot.Results and DiscussionWe optimize the total cost of the replenishment cycle, RW utility, and total items purchased. The model is illustrated with an appropriate numerical example, and extensive sensitivity analysis is conducted on the system’s performance.